2023
DOI: 10.1051/mbcb/2023006
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of two difficulty indexes in predicting the surgical extraction difficulty of impacted mandibular third molars

Abstract: Introduction: The aim of this study was to compare the reliability and the agreement of the Pederson and Pernambuco difficulty indexes in predicting the surgical extraction difficulty of the impacted mandibular third molars. Materials and methods: A prospective observational cohort study was conducted on 83 patients who had undergone surgical removal of impacted mandibular third molar. The difficulty of extraction was determined preoperatively according to the total scores obtained from the Pederson and Pernam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 23 publications
3
10
0
Order By: Relevance
“…In this study we found that impaction of lower third molar occur in female than in male, this is in accordance with research conducted by Braimah et al (21) ; Barunawaty et al (22) ; Albyati et al (23) ; and Bede (24) . This is consistent with the assumption that physical growth in woman will stop earlier compared to men and this leads to a smaller jaw size in women compared to men.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study we found that impaction of lower third molar occur in female than in male, this is in accordance with research conducted by Braimah et al (21) ; Barunawaty et al (22) ; Albyati et al (23) ; and Bede (24) . This is consistent with the assumption that physical growth in woman will stop earlier compared to men and this leads to a smaller jaw size in women compared to men.…”
Section: Discussionsupporting
confidence: 92%
“…In our study, 54 cases of impacted third molar were 32 (59.3%) right side and 22 (40.7%) left side. Similar to Albyati et al (23) stated that prevalence of impacted mandibular third molar on right side is more than left side. Also, Jae-Young et al (28) found of the 204 impacted mandibular third molar, 89 were impacted on the left side and 115 were impacted on the right side.…”
Section: Discussionsupporting
confidence: 60%
“…The current study evaluated the effects of Winter's red line, angle of impaction, and bone density (gonial and antegonial indices) on the surgical difficulty measured by the duration of extraction and surgical technique. The mean age of the participants in this study (24.78 years) was comparable with that of other studies (range, 23.6-26.16 years) [17][18][19][20]. Third molar eruption times vary by ethnic group, and it was shown that Africans' third molar eruption times are earlier than those of Caucasians and Asians [21,22].…”
Section: Discussionsupporting
confidence: 83%
“…They could range from common ones, like dry socket, to uncommon and serious ones [2]. postoperative complications, like mouth opening limitation, swelling, dry socket, pain and inferior alveolar nerve injury, however, may be associated with the extraction of an impacted third molar [3]. Further, dry socket is a post-extraction socket where some or all of the bone within this socket, or around it, are exposed in the days following the dental extraction, because the bone having not been covered by an initial and persistent blood clot or having not been covered by a layer of vital, persistent, healing epithelium [4].…”
Section: Introductionmentioning
confidence: 99%